PREVENTION OF DIVORCE THROUGH THE MOVEMENT OF THE MASTURAH PROGRAM AND ITS CONTRIBUTION TO RENEWAL OF FAMILY LAW IN INDONESIA (Case Study of the Tabligh Congregation in Lampung Province) - Suratno, S.; Baihaqi, Yusuf; Maimun, M.; Faizal, Liky (Universitas Islam Negeri Raden Intan Lampung, 2021)
Islam as a perfect religion has regulated the entire order of human life both concerning the life of the world and the hereafter, one of which is the sustainability of human descendants through a legitimate way, through marriage, where one of the goals is to form a sakinah family, but to make it happen is not as easy as turning the hand. It takes a process and cooperation between husband and wife and family members to make it happen, and it is not uncommon for households to contain various disputes with the end of divorce, especially during the current covid-19 pandemic, and to minimize this, the Tabliqh congregation of Lampung Province carries out the Masturah Program movement to prevent the increase in divorce cases in Lampung. This research is a qualitative research using an empirical juridical approach and is descriptive analytic, data analysis using inductive and deductive thinking frameworks. This study found the fact that the masturah program is very effectively used as a contemporary method to make it easier to create a sakinah family and as a renewable method as a means of mediation by the mediator so that religious courts and scholars are able to reduce divorce rates in Lampung province, especially among the Tabligh congregation community. Keywords: Divorce Prevention, Masturah Program, Tabligh Congregation.